Malaysian Capital Controls : Macroeconomics and Institutions - Tamirisa, Natalia (IMF Working Papers; Working Paper ;, 2006)
We analyze the capital controls imposed in Malaysia in September 1998. In macroeconomic terms, these controls neither yielded major benefits nor were costly. At the same time, the stock market interpreted the capital controls (and associated events) as favoring firms with stronger political connections, and some connected firms reportedly received advantages immediately following the crisis. Analysis of financial accounts indicates that connected firms outperformed unconnected firms before the 1997-98 crisis but not afterward. After the crisis, connected firms were either not supported as much as the market had expected or the benefits they received were not manifest in their published accounts.